FROM THE HISTORY OF RELIGIOUS TOLERANCE IN CENTRAL ASIA - Abror Anvarovich Аdilov (Journals Park Publishing, 2023)
In this article has been analyzed the history of religious tolerance in Central Asia by the helping historical literatures and sources as well. Besides, it showed that the establishment of the power of the Arab Caliphate in Central Asia, the ideas of Islam triumphed and Islam clearly occupied the position of monotheism, rejecting any division in relation to religion, especially polytheism and it should be noted that the ideas of monotheism ended the spiritual vacuum that existed before the advent of Islam.
Keywords: Tolerance, Central Asia, Religion, Muslim, Islam, population.